2021
DOI: 10.7554/elife.71077
|View full text |Cite
|
Sign up to set email alerts
|

Opioid antagonism modulates wanting-related frontostriatal connectivity

Abstract: Theoretical accounts distinguish between motivational (‘wanting’) and hedonic (‘liking’) dimensions of rewards. Previous animal and human research linked wanting and liking to anatomically and neurochemically distinct brain mechanisms, but it remains unknown how the different brain regions and neurotransmitter systems interact in processing distinct reward dimensions. Here, we assessed how pharmacological manipulations of opioid and dopamine receptor activation modulate the neural processing of wanting and lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
3
11
2
Order By: Relevance
“…One possibility is that opioid receptors are not crucial for model-free learning required in this task. This is in opposition to previous studies showing that acute administration of naltrexone, comparably to amisulpride, causes a reduction of cue responsivity and reward impulsivity ( Weber et al, 2016 ), decreases effort to obtain immediate primary rewards ( Korb et al, 2020 ), and decreases the wanting of rewards ( Soutschek et al, 2021 ). Similarly, preclinical studies in rats show that naltrexone and naloxone, another opioid antagonist, decreased sucrose reinforced place preference ( Delamater et al, 2000 ; Agmo et al, 1995 ).…”
Section: Discussioncontrasting
confidence: 99%
“…One possibility is that opioid receptors are not crucial for model-free learning required in this task. This is in opposition to previous studies showing that acute administration of naltrexone, comparably to amisulpride, causes a reduction of cue responsivity and reward impulsivity ( Weber et al, 2016 ), decreases effort to obtain immediate primary rewards ( Korb et al, 2020 ), and decreases the wanting of rewards ( Soutschek et al, 2021 ). Similarly, preclinical studies in rats show that naltrexone and naloxone, another opioid antagonist, decreased sucrose reinforced place preference ( Delamater et al, 2000 ; Agmo et al, 1995 ).…”
Section: Discussioncontrasting
confidence: 99%
“…One possibility is that opioid receptors are not crucial for model-free learning required in this task. This is in opposition to previous studies showing that acute administration of naltrexone, comparably to amisulpride, causes a reduction of cue responsivity and reward impulsivity 66 , decreases effort to obtain immediate primary rewards 67 , and decreases the wanting of rewards 70 . Similarly, preclinical studies in rats show that naltrexone and naloxone, another opioid antagonist, decreased sucrose reinforced place preference 71,72 .…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, only the opiodergic manipulation induced a reduction in positive facial expressions in response to liked food rewards during their consumption. These results are in line with other human studies suggesting the involvement of the dopamine system in Pavloviantriggered motivation [20][21][22][23] and the implication of the opioid system in motivational and hedonic processes [24][25][26] (but see [27], for a study suggesting that the opioid system mediates neural connectivity related to motivational, but not hedonic, processes). Furthermore, another recent study [28•] showed that the motivational and hedonic processes involved in the affective response to a reward recruit distinct subregions of the ventral striatum in humans.…”
Section: The Multicomponential Nature Of the Affective Response To Fo...supporting
confidence: 91%